CircZNF609 as a prototype to elucidate the biological function of circRNA-mRNA interactions. (31st December 2022) - Beltran, Manuel; Rossi, Francesca; Bozzoni, Irene
ABSTRACT: Circular RNAs (circRNAs) are expressed and are regulated in many biological processes but little is known about their ability to directly control mRNA homeostasis. We show that circRNA zinc finger protein 609 (circZNF609) interacts with several mRNAs increasing the final protein levels, which in the case of the cytoskeleton-associated protein 5 (CKAP5) leads to a stabilized microtubule cytoskeleton and an enhanced tumor cell proliferation.